Antiamnesic Activity of an Ayurvedic Formulation Chyawanprash in Mice. (5th June 2011) - Parle, Milind; Bansal, Nitin
Abstract : Chyawanprash (Chy) is an ayurvedic formulation commonly consumed in Indian households. Chy is a comprehensive herbal tonic, prepared from around 50 herbs employing anwala ( Emblica officinalis ) as the basic ingredient. The present study was undertaken to explore the beneficial effects of Chy (at the dose of 1 and 2% w/w of diet) administered daily for 15 successive days in mice with memory deficits. A total of 228 mice divided in 38 groups were employed in this study. Morris water maze, Hebb-Williams maze and elevated plus maze served as exteroceptive memory models, whereas scopolamine (Sco)-induced amnesia and alprazolam (Alp)-induced amnesia served as interoceptive memory models. The brain acetylcholinesterase activity, brain thiobarbituric acid reactive substances (TBARS) and reduced glutathione levels (GSH) were also estimated. The administration of Chy for 15 consecutive days significantly protected the animals from developing memory impairment. Furthermore, there was a significant decrease in brain TBARS and increase in GSH levels after administration of Chy (2% w/w), thereby indicating decreased free radical generation and increased scavenging of free radical, respectively. Thus, Chy may prove to be a useful remedy for the management of Alzheimer's disease owing to its antioxidant effect, pro-cholinergic action and/or antiamnesic potential.